Nanofibrous polycaprolactone scaffolds with adhered platelets stimulate proliferation of skin cells - Vocetkova, K; Buzgo, M; Sovkova, V; Bezdekova, D; Kneppo, Peter; Amler, Evžen (Cell proliferation, 2016)
OBJECTIVES: Faulty wound healing is a global healthcare problem. Chronic wounds are generally characterized by a reduction in availability of growth factors. New strategies are being developed to deliver growth factors more effectively. METHODS: In this study, we introduced electrospun scaffolds composed of polycaprolactone (PCL) nanofibers functionalized with adhered platelets, as a source of numerous growth factors. Three concentrations of platelets were immobilized to nanofibrous scaffolds by simple adhesion, and their influence on adhesion, proliferation and metabolic activity of seeded cells (murine fibroblasts, keratinocytes and melanocytes) was investigated. RESULTS: The data obtained indicated that presence of platelets significantly promoted cell spreading, proliferation and metabolic activity in all the skin-associated cell types. There were no significant differences among tested concentrations of platelets, thus even the lowest concentration sufficiently promoted proliferation of the seeded cells. CONCLUSIONS: Such complex stimulation is needed for improved healing of chronic wounds. However, the nanofibrous system can be used not only as a skin cover, but also in broader applications in regenerative medicine.
Keywords: melanocyty; Animals; proliferace buněk; keratinocyty; tkáňové podpůrné struktury; buněčné linie; nanovlákna; Keratinocytes; Fibroblasts; Wound Healing; trombocyty; buněčná adheze; tkáňové inženýrství; Mice; Cell Adhesion; Nanofibers; fibroblasty; myši; Blood Platelets; Polyesters; Cell Line; hojení ran; Cell Proliferation; Tissue Engineering; zvířata; polyestery; Tissue Scaffolds; Melanocytes